Developing a high-efficiency operating room for total joint arthroplasty in an academic setting. - Attarian, David E; Wahl, Jennie E; Wellman, Samuel S; Bolognesi, Michael P (Clinical Orthopaedics & Related Research®, 2013)
Background: Developing a high-efficiency operating room (OR) for total joint arthroplasty (TJA) in an academic setting is challenging given the preexisting work cultures, bureaucratic road blocks, and departmental silo mentalities. Also, academic institutions and aligned surgeons must have strategies to become more efficient and productive in the rapidly changing healthcare marketplace to ensure future financial viability.Questions/purposes: We identified specific resources and personnel dedicated to our OR for TJA, assessed the typical associated work process delays, and implemented changes and set goals to improve OR efficiencies, including more on-time starts and shorter turnover times, to perform more TJA cases per OR. We then compared these variables before and after project initiation to determine whether our goals were achieved.Methods: We gathered 1 year of retrospective TJA OR time data (starting, completion, turnover times) and combined these data with 1 month of prospective observations of the workflow (patient check-in, patient processing and preparation, OR setup, anesthesia, surgeon behaviors, patient pathway). The summarized information, including delays and inefficiencies, was presented to a multidisciplinary committee of stakeholders; recommendations were formulated, implemented, and revised quarterly. Key strategies included dedicated OR efficiency teams, parallel processing, dedicated hospital resources, and modified physician behavior. OR data were gathered and compared 3 years later.Results: After project changes, on-time OR starts increased from less than 60% to greater than 90% and average turnover time decreased from greater than 60 minutes to 35 minutes. Our average number of TJA cases per OR increased by 29% during the course of this project.Conclusions: Our project achieved improved OR efficiency and productivity using strategies such as process and resource analysis, improved communication, elimination of silo mentalities, and team work.